Effect of fabric structure on the performance of screen-printed ultra-high frequency radio frequency identification tag antenna for wireless radio frequency energy harvesting. (30th June 2022) - Zheng, Cong; Hu, Jiyong; Jiang, Jinhua
Textile materials are the ideal substrate of the antenna of eco-friendly wireless radio frequency (RF) energy harvesting technology for sustainable battery-free operation of wearable electronic devices, while few of the work published have been focused on the effect of textile properties on the energy harvesting performance. This work will clarify the effect of typical fabric surface structures on the energy harvesting performance of Radio Frequency Identification (RFID) antenna. The antennas were screen-printed onto three different weave structures, and performance for the different fabric-based antennas were studied. The results showed that the antenna printed on plain fabric, which has the smallest porosity and lower surface roughness, was able to achieve a maximum transmission distance of 110 cm and output voltage of 3.003 mV at 69 cm. Consequently, in order to improve the energy harvesting performance of antenna, the smooth and compact fabric surface is more beneficial to highly efficient energy harvesting.